Pengaruh penyesuaian diri terhadap kepuasan pernikahan pada individu yang menikah melalui proses ta’aruf - Muhammad Abbas (Fakultas Psikologi, 2019)
Satisfaction in a marriage is very important because it is a part of appraisement and evaluation, whether the marriage can to proceed or have many conflict. adjusements of a person will be the basis for the achievement of marital satisfaction, this also happens to a person who marriage trough by ta’aruf process. The research aims to investigate the influence of self-adjusment on marital satisfaction to person marriage trough by ta’aruf process. The type of research is by quantitative with 118 subjects who marriage trough by ta’aruf process. The subjects were taking by snowball sampling technique. From the retrival of data that result of the coeffition of determination or r2 = 0,268 with a significant value is 0,000 so that the self-adjustment on marital satisfaction to person who marriage trough by ta’aruf process gives a small influence with a value 26,8%.